On the pathway to an unforeseeable future: An actantial analysis of career designs of young people - Kalalahti Mira; Varjo Janne (Sage Journals, 2025)
The process of life design in contemporary adolescence is of increasing interest in times of lifelong learning and the knowledge society. The aim of this article was to increase the comprehension of career designs by analysing the two-phase interviews of 31 young people at the ages of 15 and 18. Drawing on actantial analysis, we modelled the plurality of the career designs, analysed who the main actors are in those career designs, and how young people express, exercise, and adjust their designs. We conclude that both the subjects and the objects of the young people’s career designs included multiple actors. People, issues, and circumstances are integral components of the narratives on the career designs of young people. These components bound their agency and are integrated with their orientations to education and work.